Positive Beliefs about Rumination Are Associated with Ruminative Thinking and Affect in Daily Life: Evidence for a Metacognitive View on Depression. Issue 5 (September 2014) - Kubiak, Thomas; Zahn, Daniela; Siewert, Kerstin; Jonas, Cornelia; Weber, Hannelore
<x content-type="archive" xml:space="preserve">Abstract</x> Background: Self-regulatory executive function theory (Wells and Matthews, 1994; Wells, 2008) stresses the role of metacognitions in the development of emotional disorders. Within this metacognitive model, positive beliefs about ruminative thinking are thought to be a risk factor for engaging in rumination and subsequently for depression. However, most of the existing research relies on retrospective self-report trait measures. Aims: The aim of the present study was to examine the theory's predictions with an Ecological Momentary Assessment approach capturing rumination as it occurs in daily life. Method: Non-clinical participants (N = 93) were equipped with electronic diaries and completed four signal-contingent momentary self-reports per day for 4 weeks. A multilevel mediation model was computed to examine associations between positive beliefs about rumination and ruminative thinking and negative affect in daily life. Results: Positive beliefs about rumination were significantly associated with ruminative thinking as it occurs in daily life. We further found evidence for a negative association with positive affect that was completely mediated via ruminative thinking in daily life occurring in response to negative emotions. Conclusions: Our results add ecologically valid corroborating evidence for the metacognitive model of emotional disorders within the framework of self-regulatory executive function theory.